Rehabilitación temprana de los maxilares en pacientes con labio y paladar hendido bilateral utilizando un dispositivo ortopédico dinámico intraoral, cinta adhesiva labial y gingivoperiosteoplastia: estudio piloto experimental (2009)
ABSTRACT: The purpose of this study was to corroborate the orthopaedic alveolar results of dynamic orthopaedic devices used in the pilot study by the same research group, combined with the use of an adhesive tape over the lip and gingivoperiostioplasty in a Colombian population. Methods: 6 patients with complete bilateral cleft lip and palate, 4 males and 2 females were selected out of 9 patients between five and ten months of age. The dynamic orthopaedic device and the adhesive tape were used during an average time of 3.5 weeks. After obtaining the orthopaedic result, the gingivoperiostioplasty and rhinoplasty were performed. Comparisons between before and after treatment casts were analyzed with an electronic digital calliper. The bone formation was evaluated with a dental CT scan after a period of 6 months. Descriptive statistical analysis was used. Results: every patient after orthopaedic treatment retracted the premaxilla, four of the six patients studied required anterior alveolar expansion. There was bone formation in the 8 sites where the gingivoperiostioplasty was performed. Conclusion: the use of the dynamic orthopaedic device and the adhesive tape over the lip decreased the discrepancies in maxillary segments of bilateral cleft lip and palate patients. The gingivoperiosteoplasty performed in this protocol serves as an osteo-inductor suitable for bone formation. This study corroborates the pilot study by the same research group and represents a practical option for the treatment in cases with protrusion of the premaxilar in our community.